THE EFFECT OF PRE-SOWN PRIMING OF BARLEY SEEDS IN THE SOLUTIONS OF DIFFERENT SALTS IN THE COMBINATION WITH DIATOMITE ON ALLANTOIN CONTENT IN ROOTS SEEDLINGS UNDER SALINЕ СONDITIONS - Nayekova S.K.; Aubakirova K.M.; Shalakhmetova G.A.; Demidchik V.V.; Alikulov Z. (Scientific Journal of Pedagogy and Economics, 2020)
Pre-sown priming of barley seeds in diatomite suspension in the combination with the solutions of biological important elements strongly increased their germination under saline conditions. For maximal seed germination and content of the potential antioxidantallantoinin seedling roots under salinity it was necessary the priming in the presence of diatomite, KNO3 and Na2MoO4. Role of nitrate and molybdate in maximal formation of allantoin by explained in vivo cooperations of molybdenum-containing enzymes of nitrate reductase (NR) and xanthine dehydrogenase (XDH) in the conditions of salinization. For finding out of role of diatomit further researches are required. Thus, pre-sowing treatment of plant seeds in a combination of diatomite suspension with solutions of biologically important elements dramatically increases the stability of seed germination in saline conditions. Pre-sowing seed treatment by priming is an environmentally friendly and cheap technology of pre-sowing seed treatment for saturation with important elements, which allows to do without fertilization on huge surface. This will provide the plants with important elements from the germination stage to full maturity.